O caminho para a docência: A construção do meu "eu" profissional - Cláudia Marisa Castro Machado (2020)
The training of teachers is a long and continuous process. In this sense, the school placement represents a fundamental context to experience the teaching profession with the supervision of more experienced professionals. We are, then, prepared to teach generations that have not even been born, in a school in constant change, for a permanent adaptation to the dynamic and unpredictable reality with which it is confronted. The teaching practice is the most important part of the practicum training, due to the transformations that take place in us and the effects that they provoke in the students' learning. It is so important that it allows the preservice teacher to learn, do and experiment and, in the end, build her own knowledge and identity through a real intervention, with real students and the challenges, problems, decisions and solutions that come from them. Throughout this report will be presented my history, the difficulties felt and the strategies created to solve them. The activities in which I have been involved as well as my participation within the school nucleus will also be mentioned. The choices and decisions made were aimed at providing quality teaching to students and my development as a professional. This report includes a study focused that aims to analyse the effects of a physical condition programme applied to the resident classes. It was also intended to verify the relevance of including a moment dedicated to the development of the physical fitness during the Physical Education classes. With the elaboration of this report, a long awaited step is closed. It allowed a reflection about the whole process, drawing lessons about mistakes and learning for future application.